Structural characterization of the intrinsically disordered domain of Mycobacterium tuberculosis protein tyrosine kinase A. Issue 7 (25th March 2018) - Niesteruk, Anna; Hutchison, Marie; Sreeramulu, Sridhar; Jonker, Hendrik R.A.; Richter, Christian; Abele, Rupert; Bock, Christoph; Schwalbe, Harald
Abstract : Although intrinsically disordered proteins or protein domains (IDPs or IDD) are less abundant in bacteria than in eukaryotes, their presence in pathogenic bacterial proteins is important for protein‐protein interactions. The protein tyrosine kinase A (PtkA) from Mycobacterium tuberculosis possesses an 80‐residue disordered region (IDDP tkA ) of unknown function, located N‐terminally to the well‐folded kinase core domain. Here, we characterize the conformation of IDDP tkA under varying biophysical conditions and phosphorylation using NMR‐spectroscopy. Our results confirm that the N‐terminal domain of PtkA exists as an IDD at physiological pH. Furthermore, phosphorylation of IDDP tkA increases the activity of PtkA. Our findings will complement future approaches in understanding molecular mechanisms of key proteins in pathogenic virulence. Abstract :